ANALISIS PEMANFAATAN RASI BINTANG ORION SEBAGAI INDIKATOR ASTRONOMI DALAM PENENTUAN WAKTU SALAT ISYA PERSPEKTIF ILMU FALAK - Damayanti, Riska; Agus, Jasdar (HISABUNA: Jurnal Ilmu Falak, 2025)
This research is motivated by the importance of understanding prayer times not only based on digital schedules or hisab, but also through a visual approach to natural signs, one of which is through the appearance of constellations. Orion, as a very prominent and easily recognized constellation, was chosen in this study to analyze its potential as an indicator of Isha prayer time. Based on this background, the main problem in this study is "How to Analyze the Utilization of the Orion Constellation as an Astronomical Indicator in Determining Isha Prayer Time from the Perspective of Astronomy". This study raises two problem formulations, namely how to analyze the Orion constellation as a reference in determining Isha prayer time, and how to correlate the Syafaq Ahmar phenomenon with the Orion constellation in determining Isha prayer time according to Astronomy. The purpose of this study is to find out how to analyze the Orion constellation in determining the initial time of Iysa, and to find out the relationship between the Syafaq Ahmar phenomenon and the Orion constellation in determining Isha prayer time according to Astronomy. The type of research used is a qualitative descriptive approach in the form of literature. Data were obtained through analysis of classical and contemporary literary sources, and supported by visual sky simulations using Stellarium software. The first research result shows that the constellation of Orion, specifically the star Mintaka, which appears when the Sun is at an angle of -18° and Syafaq Ahmar disappears, shows a consistent visual connection with the beginning of Isha prayer time. Therefore, it can be used as a supporting astronomical indicator in an educational context and for traditional observations according to Astronomy. Second, the correlation between the disappearance of Syafaq Ahmar and the appearance of the constellation Orion can be confirmed by sky observations from an Astronomy perspective, so both can be used as educational indicators and alternative nighttime visualizations, especially in areas with limited astronomical technology. The implications of this research, in an observational approach through visualization of the Orion constellation, can be an educational alternative in determining Isha prayer times, especially in areas with limited technology, and encourage the integration of the hisab method and sky observation in the development of Astronomy.